INTERPRETATION ULUMUL QUR’AN COURSE AS THE FOUNDATION FOR MODERATE UNDERSTANDING OF FEBI IAIN PONTIANAK STUDENTS, WEST KALIMANTAN PROVINCE - Abdurrahman Abdurrahman; Muhammad Irfan; M. Agus Muhtadi Bilhaq (Sekolah Tinggi Agama Islam Sadra, 2023)
This article reveals the existence of the “Ulumul Qur’an” course taught as the foundation for a Moderate Understanding among students of the Faculty of Islamic Economics and Business (FEBI) at the State Islamic Institute (IAIN) in Pontianak, which is located in West Kalimantan Province, a province known for its diversity in terms of ethnicity, traditions, and religions, but coexist peacefully and harmoniously in their daily lives. This article is a form of library research that uncovers the moderate values from the Ulumul Qur’an materials as well as its teaching methods. Therefore, the method used is qualitative research with a descriptive approach, where the data were collected through literature studies or documents discussing this theme, both from books and from recent online articles discussing the Ulumul Qur’an and religious moderation, and directly observed the environment at FEBI IAIN Pontianak, so that the collected data can be verified and revealed with reliable results. The instilling of moderate values towards the students of FEBI IAIN Pontianak is largely derived from the Ulumul Qur’an materials taught by a lecturer, although in delivering the material, the main focus of achievement is the understanding of the materials that have been agreed in the semester Learning Plan (RPS). The materials include Jam‘ al-Qur’ān (collection of the Qur’an), Qirā’ah al-Qur’ān (reading of the Qur’an), Asbāb al-Nuzūl (causes of the revelation of the Qur’an), and materials about the interpreters of the Qur’an, their conditions, and interpretation methods.